∫ 2 5 ( x − 2 ) 1 7 ( x − 5 ) 7 8 ( − x 3 + 9 x 2 − 2 4 x + 2 0 ) d x
If the above integral can be expressed as b ! a b c ! d ! , where b , c and d are mutually coprime integers, find a + b + c + d .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I have a question for you : Question
Log in to reply
I have a relatively easier question for u guys too ting tong
Give it a proper name Nishanth. Do you really want people to be upset by the babe if the question and not try it??
Pack some food , some water and a mind full of integration , because this solution will be a hell of a ride for you ...
Let start with the polynomial given to us − f ( x ) = x 3 − 9 x 2 + 2 4 x − 2 0
− f ( x ) − f ( x ) = ( x − 2 ) 3 − 3 x 2 + 1 2 x − 1 2 = ( x − 2 ) 3 − 3 ( x − 2 ) 2 = ( x − 2 ) 2 ( x − 2 − 3 ) = ( x − 2 ) 2 ( x − 5 )
Let I = ∫ 2 5 ( x − 2 ) 1 7 ( x − 5 ) 7 8 ( − x 3 + 9 x 2 − 2 4 x + 2 0 ) d x
− I = ∫ 2 5 ( x − 2 ) 1 9 ( x − 5 ) 7 9 d x
Let's take a general case of : I { n , m } = ∫ 1 s t f n ( x − a ) n 2 n d f n ( x − b ) m d x
I { n , m } I { n , m } I { n − 1 , m + 1 } I { n − 2 , m + 2 } I { n − 3 , m + 4 } ⋮ I { 0 , m + n } = ( x − a ) n ∫ ( x − b ) m d x − ∫ n ( x − a ) n − 1 ( ∫ ( x − b ) m d x ) d x = ( x − a ) n m + 1 ( x − b ) m + 1 − m + 1 n ∫ ( x − a ) n − 1 ( x − b ) m + 1 d x = ( x − a ) n m + 1 ( x − b ) m + 1 − m + 1 n × I { n − 1 , m + 1 } = ( x − a ) n − 1 m + 2 ( x − b ) m + 2 − m + 2 n − 1 × I { n − 2 , m + 2 } × ( m + 1 − ( n ) ) = ( x − a ) n − 2 m + 3 ( x − b ) m + 3 − m + 3 n − 2 × I { n − 3 , m + 3 } × ( m + 1 − ( n ) ⋅ m + 2 − ( n − 1 ) ) = ( x − a ) n − 3 m + 4 ( x − b ) m + 4 − m + 4 n − 3 × I { n − 4 , m + 4 } × ( m + 1 − ( n ) ⋅ m + 2 − ( n − 1 ) ⋅ m + 2 − ( n − 2 ) ) = ( x − a ) 0 m + n + 1 ( x − b ) m + n + 1 − 0 × ( m + 1 − ( n ) ⋅ m + 2 − ( n − 1 ) ⋅ m + 2 − ( n − 2 ) ⋯ m + n − ( 1 ) )
Add All the equations . We get :
I { n , m } = ( x − a ) n m + 1 ( x − b ) m + 1 + ( x − a ) n − 1 m + 2 ( x − b ) m + 2 × m + 1 − ( n ) + ( x − a ) n − 2 m + 3 ( x − b ) m + 3 × m + 1 − ( n ) ⋅ m + 2 − ( n − 1 ) ⋯ + ( x − a ) 0 m + n + 1 ( x − b ) m + n + 1 × m + 1 − ( n ) ⋅ m + 2 − ( n − 1 ) ⋅ m + 2 − ( n − 2 ) ⋯ m + n − ( 1 ) = r = 0 ∑ n ( − 1 ) n − r r ! n ! ⋅ ( m + n − r ) ! m ! ⋅ m + n + 1 − r ( x − a ) r ( x − b ) m + n + 1 − r
I { n , m } = ( n + m + 1 ) ! ( x − b ) m + 1 ⋅ n ! ⋅ m ! r = 0 ∑ n ( − 1 ) n − r ( r m + n + 1 ) ( x − b ) n − r ( x − a ) r
a = + 2 , b = + 5 , n = 1 9 , m = 7 9
I { 1 9 , 7 9 } = 9 9 ! ( x − 5 ) 8 0 ⋅ 1 9 ! ⋅ 7 9 ! r = 0 ∑ 1 9 ( − 1 ) 1 9 − r ( r 9 9 ) ( x − 5 ) 1 9 − r ( x − 2 ) r
Putting the limits
I { 1 9 , 7 9 } − I I = 0 − 9 9 ! ( 3 ) 8 0 ⋅ 1 9 ! ⋅ 7 9 ! × ( 0 9 9 ) × − 1 × − ( 3 ) 1 9 = − 9 9 ! 3 9 9 × 1 9 ! × 7 9 ! = − 9 9 ! 3 9 9 × 1 9 ! × 7 9 ! = 9 9 ! 3 9 9 × 1 9 ! × 7 9 !
Answer : 3 + 9 9 + 1 9 + 7 9 = 2 0 0
Special Case : Lower limit = a , upper limit = b
I { n , m } = 0 − ( n + m + 1 ) ! ( a − b ) m + 1 ⋅ n ! ⋅ m ! × ( 0 n + m + 1 ) × ( − 1 ) n × ( a − b ) n = ( − 1 ) n + 1 ( n + m + 1 ) ! ( a − b ) n + m + 1 ⋅ n ! ⋅ m !
Excellent Solution!
Log in to reply
Thank you , took me 3 0 min to write
there is a shortcut for this problem ?
Log in to reply
Yes, I used the Beta function midway.
Log in to reply
@Nishanth Subramanian – Can you please post your solution .
wow! u really are a patient integrator :P
β function helped midway :)
Problem Loading...
Note Loading...
Set Loading...
As Sambhrant Sachan has done,
− f ( x ) = x 3 − 9 x 2 + 2 4 x − 2 0
− f ( x ) − f ( x ) = ( x − 2 ) 3 − 3 x 2 + 1 2 x − 1 2 = ( x − 2 ) 3 − 3 ( x − 2 ) 2 = ( x − 2 ) 2 ( x − 2 − 3 ) = ( x − 2 ) 2 ( x − 5 )
Let I = ∫ 2 5 ( x − 2 ) 1 7 ( x − 5 ) 7 8 ( − x 3 + 9 x 2 − 2 4 x + 2 0 ) d x
− I = ∫ 2 5 ( x − 2 ) 1 9 ( x − 5 ) 7 9 d x
I = ∫ 2 5 ( x − 2 ) 1 9 ( 5 − x ) 7 9 d x
Now, consider the beta function I 2 (20,80) = ∫ 0 1 ( x ) 1 9 ( 1 − x ) 7 9 d x
Substitute in I 2 (20,80)
x = 5 − 2 y − 2 ⇒ d x = 3 d y
I 2 (20,80) 3 9 9 = ∫ 2 5 ( y − 2 ) 1 9 ( 5 − y ) 7 9 d y
Now, evaluating the beta function I 2 (20,80) , we get I 2 (20,80) = 9 9 ! 1 9 ! 7 9 !
Therefore the required integral is equal to 9 9 ! 3 9 9 × 1 9 ! × 7 9 !